The Origin of the Concept “Tianxia” in the Political Ideological Configuration of Traditional China - Yuchen, Zhang (Sinología hispánica. China Studies Review, 2018)
The concept "Tianxia" (All-under-Heaven) could be a parallel concept of the "Empire" in the West, which also allows a better understanding of the Chinese history with its own political language. This concept not only serves to legitimize the dominion of the Tianzi (Son of God Heaven) in China, but also makes possible a political internalization instead of the territorial expansion in the East Asian area. The "Heaven" (or Sky) is fundamental to understand the revolution of power in Ancient China, with the various meanings in which it has been interpreted. This is finally recognized as the supreme god, that the Tianzi inherited and obtained dominion over the corresponding earth. However, with the divine and ethical nature of Heaven, the dominator is required to have the virtue and good execution of power to keep the authorization in hand. With this text, the origin and the main development of the Tianxia system are revealed as the legitimizing regime of Chinese politics.